Blood lead level is a positive predictor of uremic pruritus in patients undergoing hemodialysis - Weng CH; Hsu CW; Hu CC; Yen TH; Chan MJ; Huang WH (Dove Medical Press, 2017)
Cheng-Hao Weng,1,2 Ching-Wei Hsu,1,2 Ching-Chih Hu,2,3 Tzung-Hai Yen,1,2 Ming-Jen Chan,1,2 Wen-Hung Huang1,2 1Department of Nephrology and Division of Clinical Toxicology, Chang Gung Memorial Hospital, Linkou Medical Center, 2Department of Medicine, Chang Gung University College of Medicine, Taoyuan, 3Department of Hepatogastroenterology and Liver Research Unit, Chang Gung Memorial Hospital, Keelung, Taiwan Abstract: Although uremic pruritus (UP) is a common and annoying symptom for end-stage renal disease patients on hemodialysis (HD) and peritoneal dialysis, its pathogenesis is poorly understood. However, systemic inflammation is one of the possible pathogenesis of UP, and blood lead level (BLL) has been noted to be associated with inflammation and nutritional status in long-term HD patients. There might be an interaction or association, therefore, between BLL and UP through systemic inflammation. We analyzed cross-sectional data among 866 participants. All of the 866 patients in this study were stratified into groups with low-normal (<10 µg/dL), high-normal (10–20 µg/dL), and abnormal BLLs (>20 µg/dL). The associations between UP and BLL and the clinical data were analyzed. Multivariate logistic regression demonstrated that HD duration, non-anuria, log ferritin, serum low-density lipoprotein, log BLL, high-normal BLL, and high BLL were associated with UP. In conclusion, BLL was positively associated with UP. Keywords: blood lead levels, uremic pruritus, hemodialysis